Characterization of multiple-antimicrobial-resistant Salmonella enterica Subsp. enterica isolated from indigenous vegetables and poultry in Malaysia. - Cheah, Yoke Kqueen; Lee, Learn Han; Awang Saleh, Noorzaleha; Radu, Son; Sukardi, Sabrina; Sim, Jiun Horng; Khoo, Chai Hoon (Wiley, 2008)
Aims: The aims of this communication were to study characterization of serogroups among Salmonella isolates and the relationship of antimicrobial resistance to serogroups. Multiple antimicrobial resistance (MAR) was performed on 189 Salmonella enterica isolates associated with 38 different serovars that were recovered from poultry and four types of indigenous vegetables.